design Electronic cost accounting system for the Iraqi Airways Company - صحبت, حنان; علي, محمد تحسين (Journal of Economics and Administrative Sciences, 2016)
The research Was based to on a real problem and realistically of represented by that  Iraqi Airways company does not have the electronic cost accounting system and therefore  be the process of  the pricing various services provided by a company sample research respecting  air transport and air cargo and aviation fuel and services and catering are not properly especially in the presence of new data from the new companies entering competition in Iraqi aviation industry and therefore does not provide price flexibility in order to compete in getting market share, And then research this problem addressed through design an electronic cost Accounting system covers all the costs incurred by the company in order to provide services to meet the management requirements of reports and information costs quickly and more accurately in order to help them make to the various decisions and to the accommodate a  vast amount of financial data comparison the rest of the Iraqi companies to the fact that the company sample research is the only company profitable subsidiaries  to Iraqi transport ministry, The researcher reached to a lot of conclusions, most notably is the lack of the company's ability to estimate the cost of air transport service in a scientific manner and process healthy and the required speed, accuracy, and thus was also affected the tickets that are not realistic pricing process, as well as also the case in the rest of the services provided by the company.